Effect of glucosamine and its peptidyl-derivative on the production of extracellular matrix components by human primary chondrocytes. Issue 1 (January 2015) - Stoppoloni, D.; Politi, L.; Leopizzi, M.; Gaetani, S.; Guazzo, R.; Basciani, S.; Moreschini, O.; De Santi, M.; Scandurra, R.; Scotto d'Abusco, A.
Summary: Objective: Aim of this study is to investigate the effects of Glucosamine (GlcN) and its peptidyl-derivative, 2-(N-Acetyl)-l -phenylalanylamido-2-deoxy-β-d -glucose (NAPA), on extracellular matrix (ECM) synthesis in human primary chondrocytes (HPCs). Methods: Dose-dependent effect of GlcN and NAPA on Glycosaminoglycan (GAG), Collagen type II (Col2) and Small Leucine-Rich Proteoglycans (SLRPs) was examined by incubating HPCs, cultured in micromasses (3D), with various amounts of two molecules, administered as either GlcN alone or NAPA alone or GlcN plus NAPA (G + N). Immunohystochemical and immunofluorescent staining and biochemical analysis were used to determine the impact of the two molecules on ECM production. Gene expression analysis was performed by TaqMan Real-Time Polymerase Chain Reaction (PCR) assays. Results: The lowest concentration to which GlcN and NAPA were able to affect ECM synthesis was 1 mM. Both molecules administered alone and as G + N stimulated GAGs and SLRPs synthesis at different extent, NAPA and mainly G + N stimulated Col2 production, whereas GlcN was not effective. Both molecules were able to induce Insulin Growth Factor-I (IGF-I) and to stimulate SOX-9, whereas NAPA and G + N were able to up-regulate both Hyaluronic Acid Synthase-2 and Hyaluronic acid. Very interesting is the synergistic effect observed when chondrocyte micromasses were treated with G + N. Conclusions: The observed anabolic effects and optimal concentrations of GlcN and NAPA, in addition to beneficial effects on other cellular pathways, previously reported, such as the inhibition of IKKα, could be useful to formulate new cartilage repair strategies.